More is not always better: evidence from a randomised experiment of computer-assisted learning in rural minority schools in Qinghai. Issue 4 (1st October 2016) - Lai, Fang; Zhang, Linxiu; Bai, Yu; Liu, Chengfang; Shi, Yaojiang; Chang, Fang; Rozelle, Scott
ABSTRACT: The education of poor and disadvantaged populations has been a long-standing challenge for education systems in both developed and developing countries. Drawing on data from two randomised controlled trials involving two cohorts of grade 3 students in poor rural minority schools in China's Qinghai province, this paper explores the effects of computer-assisted learning (CAL) on student academic and non-academic outcomes for underserved student populations, and how interactions between the CAL programme and existing classroom resources affect the programme effectiveness. Results show that CAL could have significant beneficial effects on both student academic and non-academic outcomes. However, when the scope of the programme expanded to include a second subject (in this case, math – which was added on top of the Mandarin subject matter that was the focus of the first phase of the programme), some schools had to use regular school hours for CAL sessions. As a result, the phase II programme did not generate any (statistically) significant improvement over the first phase.